A comparative study on quality of life of elderly among those living with families and in old age homes in a District in South India - Nawin Jai Vignesh; Neethu George; S Hemadharshini (Journal of the Indian Academy of Geriatrics, 2022)
Introduction: The elderly population in India is steadily increasing and it is expected to triple in 2050 as of the census 2011. Drastic improvements in health care made betterment in physical health but their subjective well-being remains unaccounted. Therefore, the present study aims to assess the quality of life (QoL) among elderly and to compare the differences in QoL among elderly population residing in homes and in old age homes. Methodology: An analytical cross-sectional study among elderly above the age of 60 years residing with families and other 40 elderly population residing in old age homes. A questionnaire-based interview was conducted using a standard semistructured World Health Organization-BREF QoL questionnaire. Results: In the study, most of the participants 45 (56.3%) were male and 35 (43.8%) belonged to the age group of 70–79 years with a mean (standard deviation) age of 73.96 (7.44) years. The study found that there is nil significant difference in QoL among elderly living in old age homes and in family setups. The domain scores of psychological, social, and environmental domains showed a slight nonsignificant increase in elderly among old age homes. Conclusion: The study showed nil significant difference in QoL score in all domains for the elderly. The concept of QoL needs to be looked into with more preference to psychological, social, and environmental domains.